The Tradition of Granting Panyanda by Heirs to Nieces and Nephews in Siulak District: An Analysis from Islamic Law Perspective - Sholeh, Amid; Afridawati, Afridawati (Pendidikan Agama Islam STIT Palapa Nusantara, 2026)
Although customary gift-giving practices related to inheritance have long shaped kinship relations within plural legal settings, the Pianda/Panyanda tradition remains underexplored despite its important implications for family dynamics and the application of Islamic law. This study analyzes the implementation of the Pianda/Panyanda tradition by heirs toward nieces and nephews, its positive and negative effects on kinship relations and social order, and its position within the framework of Islamic law. Employing a qualitative case study design in Siulak District, the research involved 15 purposively selected key informants, comprising customary leaders, religious figures, heirs, and family representatives. Data were collected through semi-structured interviews, participant observation, and documentary analysis, and were analyzed thematically. The findings show that Panyanda functions as a binding customary institution embedded in adat law, enforced through moral and material sanctions and regulated through specific ritual procedures. The tradition produces dual consequences: it reinforces extended family solidarity, genealogical awareness, and moral responsibility, while also creating risks of social tension and economic pressure when obligations are not fulfilled. From the perspective of Islamic law, Panyanda is distinct from farāʾiḍ-based inheritance and is better understood as a customary obligation consistent with ʿurf, hibah, and waṣiyyah, provided that the rights of legal heirs are not infringed. The study concludes that Panyanda is a context-dependent practice whose legitimacy depends on justice, consent, and maṣlaḥah. This study contributes to scholarship on legal pluralism by clarifying the interaction between customary norms and Islamic legal principles and offers practical insight for the accommodation of customary and religious practices in family relations.